2013
DOI: 10.7751/cunninghamia.2013.005
|View full text |Cite
|
Sign up to set email alerts
|

Reassessment of the invasion history of two species of Cakile (Brassicaceae) in Australia.

Abstract: Abstract:In this paper we revisit the invasion history of two species of Cakile in Australia. Cakile edentula subsp. edentula arrived in the mid 19 th Century and spread into coastal strandline habitat from the southeast towards the west and to the north; Cakile maritima arrived in the late 19 th Century and has replaced Cakile edentula over much of the range. While Cakile edentula is morphologically quite uniform, the great variation within Cakile maritima has confused field ecologists. Using herbarium record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
41
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(48 citation statements)
references
References 31 publications
6
41
1
Order By: Relevance
“…appeared in Australia first and spread widely. It was first collected in Victoria, eastern Australia, in 1863 and was soon found in the neighbouring states; it was found in Queensland in 1922 (Rodman, 1986;Cousens et al, 2013). It appears only to have reached the eastern-most extremities of Western Australia.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…appeared in Australia first and spread widely. It was first collected in Victoria, eastern Australia, in 1863 and was soon found in the neighbouring states; it was found in Queensland in 1922 (Rodman, 1986;Cousens et al, 2013). It appears only to have reached the eastern-most extremities of Western Australia.…”
Section: Introductionmentioning
confidence: 99%
“…Two-dimensional geographical arenas, often accompanied by sporadic geographical leaps and back-filling (Cousens et al, 2008) and with poor historical information, mean that invasion histories are very difficult to reconstruct with confidence. Inferences made from spatial surveys after the invasion has progressed for many years (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, we show in a case study using a simplified version of the model that the parameter values required for the demographic mechanism to be as effective as genetic changes in fitness are fulfilled by the sequential invaders Cakile edentula and Cakile maritima. Our hypothesis therefore provides a possible explanation for the rapid replacement of C. edentula over a large part of its invasive range by C. maritima in the west of North America, New Zealand, and Australia (12)(13)(14)(15).…”
mentioning
confidence: 99%
“…Rodman 1986;Heyligers 2007). Cousens et al (2013) reviewed the history of invasion of Cakile in Australia and found that Cakile maritima was introduced into Australia from morphologically distinct races. This explains the regional variation within Australia and the high variability in the appearance of this taxon in the southeast, without the need for introgression of Cakile edentula into Cakile maritima.…”
Section: Introductionmentioning
confidence: 99%